HUBUNGAN RUMAH PENGOLAHAN SPUTUM(BALE HANUM) DENGAN PENEMUAN KASUS TBC (CDR)DI KOTA MATARAM - Nurhayati Darwan; Sukardin; Rahmani Ramli; Baiq Rahmawati Ariani; I Gusti Ayu Mirah Adhini; Ageng Abdi Putra (LPPM STIKES Mataram, 2025)
Pulmonary Tuberculosis (TB) is a disease caused by the bacteria mycobacterium tuberculosis. TB is currently still a public health problem both in Indonesia and internationally, making it one of the sustainable health development goals of the 17 points of Sustainable Development (SDGs). Tanjung Karang Health Center was appointed as a Referral Health Center because it already has a bale hanum house (sputum processing) Satellite Referrals, including those obtained from networks and several referrals from other satellite laboratories using the TCM (Molecular Rapid Test) method which actively plays a role in efforts to eliminate TB disease in accordance with the Government program stated in the Presidential Regulation of the Republic of Indonesia Number 67 of 2021 concerning TB Control The purpose of this study was to determine the relationship between sputum processing houses (Bale Hanum) and TB Case Discovery (CDR) in Mataram City. This research method is quantitative and the sampling technique uses accidental sampling, a total population of 100 samples. The results of the study There is a relationship between sputum processing houses (Bale Hanum) at the Tanjung Karang Health Center and the discovery of TB cases (CDR) in Mataram City. And from the two variables, it is interpreted that there is a significant relationship (meaningful) with a p value of 0.000 (p <0.05). The conclusion of this study There is a relationship between sputum processing houses (Bale Hanum) with the discovery of TB cases (CDR) in Mataram City